Ice shelf break-up and ecosystem loss in the Canadian High Arctic - Mueller, D.R.; Jeffries, M.O.; Vincent, W.F. (Eos, Transactions American Geophysical Union, 2003)
Over the last 3 years, extensive fractures have appeared in the ∼3000-yr-old Ward Hunt Ice Shelf (83°N,75°W).The largest fracture, a north-south-oriented serpentine feature (Figure l), now forms an obvious dividing line between the west and east sides of the ice shelf. Secondary fractures extending westward from the central fracture have fragmented a large area of the ice shelf into free-floating ice blocks. The fractures have severely weakened the ice shelf, although for the moment it remains pinned in place by a number of islands and ice rises. An immediate consequence of the fracturing was the catastrophic drainage of a fresh water lake that was dammed behind the ice shelf. This “epishelf” lake represented a rare ecosystem type in the northern hemisphere, which was particularly vulnerable to climate change. In a recent paper in Geophysical Research Letters [Mueller et al., 2003], a recent 30-year period of accelerated warming, part of a longer 20th-century warming trend, is implicated as a factor in the fracturing of the ice shelf and the drainage of the epishelf lake.